Investigating a twinning–detwinning process in wrought Mg alloys by the acoustic emission technique. (15th May 2016) - Drozdenko, Daria; Bohlen, Jan; Yi, Sangbong; Minárik, Peter; Chmelík, František; Dobroň, Patrik
Abstract: Two extruded magnesium alloys, AZ31 with a bimodal microstructure and ZE10 with a homogeneous microstructure, were pre-compressed and subsequently subjected to tensile loading. The acoustic emission (AE) technique was concurrently applied to determine the activity of particular deformation mechanisms. Significant changes in the AE response were correlated with the inflection points on the tensile curve. Twinning and detwinning processes were analyzed using the AE dataset. Particularly, nucleation of various types of twins and the influence of twins produced by pre-straining on the subsequent hardening behavior were investigated in detail. The output of the AE analysis was related to microstructure observations provided by the electron backscattered diffraction (EBSD) method. Graphical abstract: